Hematologic manifestations of coronavirus disease 2019 in children: Case-series report and a review - Onimoe, Grace; Alvarado, Juan; Boakye, Anita (Frontiers in Pediatrics, 2022)
On March 11, 2020, COVID-19 caused by SARS-CoV-2 was declared a pandemic by the World Health Organization (WHO). As the COVID-19 pandemic has ravaged worldwide, children have not been unaffected. Information gleaned from adult experience with the disease, has aided in disease detection and treatment strategies in children. Numerous cases have been described in adult literature about hematologic manifestations of COVID-19. This case series aims to report several hematologic presentations in patients with COVID-19 and/or Multisystem Inflammatory Syndrome- in Children (MIS-C - an immune-mediated reaction leading to severe covid-19 illness) with and without a primary hematologic disorder.